Reforma psiquiátrica brasileira e o desafio de cuidar em liberdade: reflexões sobre casos de alta em um CAPS - Frazatto, Carina Furlaneto (2018)
This study aims to reflect on the freedom health care, as proclaimed by the Psychiatric Reform, and how it has been effected under the SUS. Considering that mental health care in Brazil, historically marked by isolation in psychiatric institutions, has gradually been replaced by care in the Psychosocial Care Network (RAPS), this study comprises the freedom health care as opposed to isolation practices, whether performed in psychiatric hospitals or reproduced in mental health services out of it. It understands that the implementation of the new model of mental health care, regulated since 2001, through the Law 10.216, is the result of intense struggle by social movements in favor of the Psychiatric Reform, whose principles were in part embraced by public policies of health. The process of realization has taken place under controversies and challenges that need to be constantly discussed. This study is within the context of reviewing the scope and difficulties faced, proposing, as methodological point, the collection of data in medical records of users who were discharged from CAPS 1 of Marialva-PR during the year of 2015. Through the information collected: 1) we draw the profile of users in terms of age, marital status, schooling and occupation; 2) we constructed an overview of the care received by them, taking into account the origin of referrals, initial complaints, diagnostic classification, duration of medical monitoring, prevalence of psychiatric hospitalization, access to social benefits and the variety of registered interventions for the team; 3) we analyzed the aspects directly related to the medical discharge of the CAPS, identifying the professionals who recorded it in the medical record, the issues addressed around this procedure, the contact with the RAPS, the referrals made and the participation of the users in specific activities at the time of discharge . It was possible to recognize signs that suggest the realization of freedom health care. Diagnostic complaints and classifications confirm that the CAPS of Marialva-PR complies with the recommendations of the National Mental Health Alcohol and Other Drugs Policy regarding the public served, which is composed of people with severe and persistent mental disorders. The reduced number of patients referred for hospitalization during the period of medical monitoring in this CAPS and their accomplishment in the Psychiatric Emergency of a general hospital show that it is possible to achieve mental health care according to the principles of the Psychiatric Reform. The interdisciplinarity present in most of the interventions carried out by the team and in the preparation of the Therapeutic Projects also contributed to the effectiveness of this process. On the other hand, we identified incidents, such as the reception of users before the first psychiatric hospitalization, the indispensable nature of the medication, the expansion of interventions that go beyond the service space and ensure permanent contact with RAPS not only at the moment of discharge, but throughout the monitoring. Such difficulties are associated with the way in which we have historically understood and dealt with madness in our society and, when discussed in the light of epistemological questions, point to the existence of issues of the classical paradigm of psychiatry which need to be overcome. Thus, this study instigates the need to uncover traps that may constitute impediments and setbacks to the Psychiatric Reform, a field in permanent construction, for which we hope to contribute facing the challenge of caring in freedom health care